Keberhasilan Hukum Islam Menerjang Belenggu Kolonial dan Menjaga Keutuhan Nasional - Faiq Tobroni (Unisia, 2009)
The receptie exit theory of Hazairin has freed Islamic Law from legal colonization as aresult of the receptie theory. Since the independence day, the receptie theory has not beeneffective any longer, because since then Pancasila has been the main source of laws,including Islamic Law, without any subordination. However, the inclusion of the word “Islam”in the previous Pancasila, known as Piagam jakarta, had been controversial. Nevertheless,Hatta had been successful to cope with the problem by substituting the controversialword in the first principle to the symbolic word of “Oneness” which remains tocontain Islamic spirit. This choice has succeeded to defend Indonesian state integrity.Keywords: receptie exit, receptie, colonization, state integrity.